2018
DOI: 10.1039/c8ra04525a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on cure kinetics of epoxy resin containing carbon nanotubes modified with hyper-branched polyester

Abstract: The cure kinetics of epoxy resin cured by D-EP, D-EP/CNT composites and D-EP/CNTs-H20 were investigated by non-isothermal differential scanning calorimetry (DSC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…The addition of o‐CNTs does not lead to great differences when added to the curing formulation. In all the CNT‐filled formulations, the temperature of the maximum of the peak is reduced only by 2 °C, which indicates a slight activation of the curing process as reported previously . The addition of 40 wt% of BN to the neat epoxy leads to a similar decrease in the temperature of the peak, but there is no influence on the CNT‐filled formulations.…”
Section: Resultssupporting
confidence: 79%
“…The addition of o‐CNTs does not lead to great differences when added to the curing formulation. In all the CNT‐filled formulations, the temperature of the maximum of the peak is reduced only by 2 °C, which indicates a slight activation of the curing process as reported previously . The addition of 40 wt% of BN to the neat epoxy leads to a similar decrease in the temperature of the peak, but there is no influence on the CNT‐filled formulations.…”
Section: Resultssupporting
confidence: 79%
“…Hyperbranched polyester, which has a lower branching efficiency than dendrimers, has been deeply studied due to its excellent performance and wide application [19,20]. The highly branched architecture helps to minimize low melt viscosity and chain-chain ability of the hyperbranched polyester, which is favorable for improving the compatibility with iPP [21]. The existence of multitudinous functional groups, such as hydroxyl groups, provides high reactivity with reinforced fillers, which makes hyperbranched polyester suitable as the ideal surface modifier for graphene oxide, thereby further improving the dispersion and compatibility in iPP.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer science potentially offers the most promising opportunities by finding novel means to change the surface chemistry of the nanofiller and thus improve epoxy and nanofiller affinities. Work elsewhere (Lu et al, 2018) demonstrated that cure temperature and activation energy reduced after adding CNT to Epon 825 epoxy resin cured with diethyltoluene diamine. This shows the complexity of the challenge and that collaboration between materials scientists and polymer chemists is crucial to developing a full understanding of how graphene derived nanofillers can best be incorporated into the matrix phase.…”
Section: Go/epoxy Resin Matrixmentioning
confidence: 99%
“…It should be also be appreciated that the modification of GO might influence the curing kinetics, which is very important in understanding the impact of modified nanofillers on the performance of hybrid composites. For instance, Lu et al (2018) conducted to comparatively investigation on the role of hyperbranched polyester surface modification of CNTs in the cure kinetics of the epoxy resin cured by diethyltoluene diamine (D-EP), D-EP/multi-walled carbon nanotube(D-EP/CNT) composites and D-EP/hyper branched polyester functionalized CNTs (D-EP/CNTs-H20) by nonisothermal differential scanning calorimetry (DSC). Their results revealed that the presence of CNTs shifted the cure temperature to a lower temperature and accelerated the curing of D-EP, and the addition of CNTs-H20 exhibited a stronger effect in accelerating the cure of D-EP.…”
Section: Go/epoxy Resin Matrixmentioning
confidence: 99%